Foreign Propaganda in the Electronic Press about the Syrian Crisis A Comparative Study of the Sites of Russia Today and Alhurra - A research drawn from a Master Degree thesis - Nafel al - Dulaimi, Nazhat Mahmoud; Abd Abd AL.Hussan, Adnan (ALBAHITH ALALAMI, 2025)
The research problem lies in the ambiguity of the usage of propaganda contents by two main media outlets (the Russian RT and American Alhurra) in their news coverage of the Syrian crisis through their websites and the methods used by them to convince users taking into account the mutual propaganda conflict between the United States and Russia in the war against Syria. The objectives of the research can be represented by the following: investigating the contents of American and Russian electronic propaganda towards Syrian crisis.• Identifying the contents that received most of the coverage in the Syrian crisis by the two news outlets. • Identifying the terms and phrases that have been most used by the websites of RT and Alhurra. • Investigating the diversity in the use of explanatory and persuasive techniques such as info graphic by both websites.The research can be classified under descriptive researches. The survey methodology has been adopted and the content analysis has been used. The research population consists of all the news reports that were published on RT and Alhurra websites on Syrian crisis from 11/ 01/ 2006 to 12/ 31/ 2006 according to the comprehensive sampling method. The number of the news reports that were analyzed was (466), (327) from RT website and (89) from Alhurrah. The research tools included (scientific observation), interview and (coding scheme). The most important results of the research are:1. The Syrian president Bashar al-Asad: the Russian propaganda focused on supporting him, and to ensure that he remained in office, while US propaganda focused on removing him from power.2. The characters of the presidents: the Russian propaganda focused on the character of the Russian president Vladimir Putin, while the American propaganda did not amplify the character of US president Barack Obama. 3. The style of repetition ranked first among the other Russian propaganda styles in support of its ally al-Asad in the battle of Aleppo, while the distortion style ranked first among the American propaganda styles to show a negative image of al-Asad and his allies. 4. The Russian propaganda described the Russian-Syrian operations as (liberation operations), while the American propaganda described it as (brutal murdering), (random bombing), (crimes against humanity), (war crimes), and (massacre). 5. Al-hurrah website has not used an infographic, while the RT website has published 3 info graphs that denote the Russian propaganda dependence on diversity in electronic journalism by following intimidation policy with the enemies to manifest the Russian military power during Aleppo battle.